An Analysis of Denotative and Connotative Meaning in Students’ Utterances in the Campus Environment - Moria Afriani Stefani Silaban; Bernieke Anggita Ristia Damanik (Journal of Golden Generation Multidisciplinary, 2026)
This research is designed to examine how students use both denotative and connotative meanings in their everyday utterances within the campus environment. In daily communication, students do not rely solely on literal meanings; instead, their language often conveys implied messages shaped by context, cultural background, and patterns of social interaction. To explore this phenomenon, the study applies a qualitative descriptive approach, focusing on naturally occurring conversations among students in various campus settings. Data were collected through careful observation and documentation of students’ spoken interactions, allowing for an in-depth understanding of how meaning is constructed in real-life situations. The results indicate that students actively employ both denotative and connotative meanings in their speech. However, connotative meanings appear more dominant, particularly in informal contexts such as casual conversations with peers. This tendency highlights the role of language as a flexible and dynamic tool for expression. Furthermore, the frequent use of connotative language demonstrates students’ creativity in conveying ideas, emotions, and attitudes. It also reflects how language functions as a marker of social identity, helping students build relationships and express group belonging within the academic community.